2019
DOI: 10.1097/aud.0000000000000689
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment and Perceived Clarity of Predictable Speech

Abstract: The precision of stimulus-driven information is less critical for comprehension when accurate knowledge-based predictions of the upcoming stimulus can be generated. A recent study in listeners without hearing impairment (HI) has shown that form-and meaning-based predictability independently and cumulatively enhance perceived clarity of degraded speech. In the present study, we investigated whether formand meaning-based predictability enhanced the perceptual clarity of degraded speech for individuals with moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
27
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(31 citation statements)
references
References 39 publications
4
27
0
Order By: Relevance
“…Although Nieuwland et al (2018) were unable to replicate the N400 effect demonstrated in the study by DeLong et al (2005), Nieuwland (2019) suggested that pre-activation of form is apparent in earlier brain responses. This hypothesis is in line with previous results showing that the perceived clarity of speech was greater when contingent on form-based predictions rather than meaning-based predictions, especially under adverse listening conditions (see Signoret et al, 2018;Signoret and Rudner, 2019). The difference in speech processing between form-and meaning-based predictions might then be observed on early neural activity, such as in the Mismatch Negativity (MMN) amplitudes.…”
Section: Form-based Prediction Effects On Speech Processingsupporting
confidence: 90%
See 3 more Smart Citations
“…Although Nieuwland et al (2018) were unable to replicate the N400 effect demonstrated in the study by DeLong et al (2005), Nieuwland (2019) suggested that pre-activation of form is apparent in earlier brain responses. This hypothesis is in line with previous results showing that the perceived clarity of speech was greater when contingent on form-based predictions rather than meaning-based predictions, especially under adverse listening conditions (see Signoret et al, 2018;Signoret and Rudner, 2019). The difference in speech processing between form-and meaning-based predictions might then be observed on early neural activity, such as in the Mismatch Negativity (MMN) amplitudes.…”
Section: Form-based Prediction Effects On Speech Processingsupporting
confidence: 90%
“…Even though it has been observed in several studies that predictions can be generated at multiple levels (e.g., phonological, semantic) during language comprehension (for a review, see Kuperberg and Jaeger, 2016), it remains unclear whether deviations from expectations at different levels have a different impact on speech processing (for a review, see Nieuwland, 2019). Numerous studies have shown that predictions about the form (i.e., phonology) and the meaning (i.e., semantics) of speech increase both its intelligibility (e.g., Miller et al, 1951;Davis and Johnsrude, 2007;Zekveld et al, 2011Zekveld et al, , 2013 and its perceptual clarity (Wild et al, 2012;Signoret et al, 2018;Signoret and Rudner, 2019). This facilitative effect could explain the enhanced perception of a speech event for which we already have knowledge stored in long-term memory -a phenomenon that leads to improved speech detection at a phonological level (see the "speech detection effect" in Signoret et al, 2011), better speech recognition at a lexical level (see the "word detection effect" in Signoret et al, 2011), and facilitated speech categorization at a semantic level (Daltrozzo et al, 2011;Rönnberg et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve understanding of a spoken message, the incoming speech signal has to be mapped onto knowledge representations stored in long-term memory (Rönnberg et al, 2013, 2019). Phonological representations of the sounds of words, which are dissociable from their lexical representations (Cutler, 2008), are fundamental to this process (Marslen-Wilson, 1987; Luce and Pisoni, 1998), and their importance increases when contextual or lexical information is impoverished (Mattys et al, 2005; Signoret and Rudner, 2019). When conditions for speech perception are optimal (Mattys et al, 2012), the process of matching the speech signal to phonological representations stored in long-term memory is seamless.…”
Section: Introductionmentioning
confidence: 99%